MODEL TANAMAN HORTIKULTURA ORGANIK PADA UNIT PELAKSANA TEKNIS PERTANIAN TERPADU UNIVERSITAS LANCANG KUNING - Ervayenri Ervayenri; Lativa Siswati (Universitas Lancang Kuning, 2016)
This study identify model organic horticultural crops organic . Organic agriculture to make fertilizer derived from cow urine and contain no chemicals. This means the resulting waste will be recovered into a resource that can produce. In this study the objectives is to find organic horticultural crops. Knowing the kind of revenue horticuture, implementing agribusiness development seed crop with cow urine fertilizer on agricultural land with an integrated economic benefits and ecological. The research method is experimental, horticultural crops planted kale, cucumber, pare, squash Technical Implementation Unit Univ.Lancang Kuning Pekanbaru. This study may provide a model of organic horticultural crops as well as reducing the cost of agricultural fertilizers.The results of the research model plant long beans given cow urine fertilizer is best. Cultivation of vegetables in Agricultural Technical Implementation Unit integrated crop yields obtained with the use of liquid urine fertilizer increased plant weight . Integrated agricultural income Rp 514.000- per period.